Identifying proteins bound to native mitotic ESC chromosomes reveals chromatin repressors are important for compaction - Dounia Djeghloul (Nature Portfolio, 2020)
Epigenetic information is transmitted from mother to daughter cells through mitosis. Here, the authors isolate native chromosomes from metaphase-arrested cells and perform LC-MS/MS to identify chromosome-bound proteins in pluripotent stem cells during mitosis and reveal that PRC2, DNA methylation and Mecp2 are required to maintain chromosome compaction.